Módulos e grupos abelianos finitamente gerados - Jesus, Elisângela Valéria de (2017)
The concept of module M on a ring A can be seen as a generalization of the concept of vector space V over a field K. In this work, we will present definitions, examples and results about modules, our main objective being to demonstrate the theorem of structures for Abelian groups that tells us that every finitely generated abelian group is the direct sum of cyclic subgroups.